Multicenter evaluation of efficacy and safety of low‐dose versus high‐dose valganciclovir for prevention of cytomegalovirus disease in donor and recipient positive (D+/R+) renal transplant recipients. Issue 6 (7th November 2016) - Heldenbrand, Seth; Li, Chenghui; Cross, Rosemary P.; DePiero, Kelly A.; Dick, Travis B.; Ferguson, Kara; Kim, Miae; Newkirk, Erin; Park, Jeong M.; Sudaria‐Kerr, Janice; Tichy, Eric M.; Ueda, Kimi R.; et al.
Abstract: Background: The cytomegalovirus (CMV) donor‐positive/recipient‐positive (D+/R+) population is the largest proportion of renal transplant recipients (RTR). Guidelines for prevention of CMV in the intermediate‐risk D+/R+ population include prophylaxis with valganciclovir (VGCV) 900 mg/day for 3 months. This study is the first head‐to‐head analysis, to our knowledge, comparing the efficacy and safety CMV prophylaxis of VGCV 450 vs 900 mg/day for 3 months in D+/R+ RTR. Methods: A multicenter, retrospective analysis evaluated 478 adult RTR between January 2008 and October 2011. Study participants received VGCV 450 mg/day (Group 1; n=398) or 900 mg/day (Group 2; n=89)×3 months for CMV prophylaxis. All VGCV was adjusted for renal function. All groups included in this study received study‐approved induction and maintenance immunosuppression regimens. The primary endpoint was incidence of CMV disease at 12 months. Results: The rates of graft loss, patient survival, T‐cell and/or antibody‐mediated rejection, hematological adverse events, opportunistic infections, and early VGCV discontinuation were evaluated. Patient demographics were comparable, but had significant differences in ethnicity and donor type between the groups. Conclusion: The occurrence of CMV disease at 12 months was similar between the groups (3.5% vs 3.4%; P =1.000). Log‐rank test found no statistically significant difference in the time to development of CMV between the 2 groups ( P =.939).